2000
DOI: 10.1038/sj.mp.4000678
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of the short allele of the serotonin transporter promoter gene polymorphism (5-HTTLPR) with violent suicide

Abstract: There is abundant evidence that the serotonin (5-HT) system is modulating mood and several behavioural traits and that disturbances in the regulation of this system can be associated with severe behavioural malfunctions, as aggressive implusive and suicidal behaviour. 1 Recently a functional polymorphism in the promoter region of the serotonin transporter gene (5-HTTLPR) was identified 2 and the presence of one or two short alleles was associated with anxiety-related personality traits 3 and several psychiatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
85
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(100 citation statements)
references
References 25 publications
8
85
2
5
Order By: Relevance
“…We have carried out a study using genomic DNA from 58 Caucasian suicide victims and found an association of the S-allele and completed, mainly violent, suicide (OR = 2.08; 95%CI 1.3-3.2; P = 0.001). 77 This finding could be replicated in a subsequent study with 51 Caucasian depressed, violent suicide attempters, 78 but not with suicide victims from an isolated Canadian 79 or American population. 75 In agreement with our results, an association was found between the S-allele and violent suicide attempts of Caucasian bipolar 80 and schizophrenic patients, 81 although in the latter study there was no correlation between the genotypes and impulsivity, assessed with the BIS (Barratt's Impulsivity Scale).…”
mentioning
confidence: 57%
“…We have carried out a study using genomic DNA from 58 Caucasian suicide victims and found an association of the S-allele and completed, mainly violent, suicide (OR = 2.08; 95%CI 1.3-3.2; P = 0.001). 77 This finding could be replicated in a subsequent study with 51 Caucasian depressed, violent suicide attempters, 78 but not with suicide victims from an isolated Canadian 79 or American population. 75 In agreement with our results, an association was found between the S-allele and violent suicide attempts of Caucasian bipolar 80 and schizophrenic patients, 81 although in the latter study there was no correlation between the genotypes and impulsivity, assessed with the BIS (Barratt's Impulsivity Scale).…”
mentioning
confidence: 57%
“…This finding was supported by another group who found that subjects with the ll genotype had significantly higher scores on Beck's Hopelessness Scale and Beck's Scale for Suicide Ideation than subjects with either the ls or ss genotype (Russ et al, 2000). In contrast, three other groups of researchers observed an association between the s allele and violent suicidal behavior, while a fourth found a link between the s allele and the number of lifetime suicide attempts and lethality of the suicidal behavior (Bellivier et al, 2000;Bondy et al, 2000;Gorwood et al, 2000;Courtet et al, 2001).…”
Section: Genetics Of Sertmentioning
confidence: 84%
“…Seven of these studies failed to demonstrate any link between suicidal behavior and SERT genotype or 5-HTTLPR allele frequency (Ohara et al, 1998;Chong et al, 2000;Geijer et al, 2000;Ho et al, 2000;Mann et al, 2000;Fitch et al, 2001;Rujescu et al, 2001). The remaining seven studies all found some association, albeit with differing results (Du et al, 1999;Bellivier et al, 2000;Bondy et al, 2000;Gorwood et al, 2000;Russ et al, 2000;Courtet et al, 2001;Baca-Garcia et al, 2002). One study demonstrated a higher frequency of the l allele in depressed suicide victims compared to nonsuicidal controls (Du et al, 1999).…”
Section: Genetics Of Sertmentioning
confidence: 99%
See 1 more Smart Citation
“…One very small study on completed suicide in depression showed an increase of L subjects (Du et al 1999). Three studies showed an increase of S subjects in attempters: one study in completed suicides (Bondy et al 2000); one study on violent suicide attempts in depressive patients (Bellivier et al 2000), and another on more lethal attempters in alcoholic patients (Gorwood et al 2000). No gender differences were explored in any of these studies.…”
mentioning
confidence: 99%